Mapping the policy process in Nigeria: Examining linkages between research and policy - Aberman, Noora-Lisa; Schiffer, Eva; Johnson, Michael E.; Oboh, Victor (International Food Policy Research Institute, 2009)
How research can feed into the policy process in developing countries in general, and in Nigeria more specifically, is not very well understood. Yet, this understanding is a critical part of doing effective policy research. This has become especially critical for the International Food Policy Research Institute (IFPRI), which has set up a country office for policy research in Nigeria. A key challenge for IFPRI, and other research organizations in the country, is how to better integrate research results into policy and communicate research results to Nigerian policymakers. To gain some useful insights into how research does, or does not, influence policy in Nigeria, we examined a case involving the process leading up to the adoption of the National Fertilizer Policy for Nigeria in 2006. Rather than focusing on how research influences policy in general, examining a particular policy allowed us to trace the actual policy process that took place, the actors involved, and the type of links and interactions between them. A diverse group of stakeholders (government, donors, research community, farmer organizations, and the private sector) undoubtedly debated the content of the fertilizer policy. Thus, its successful formulation and adoption offered a useful opportunity to examine how it came about in spite of competing vested interests (for or against it), and what role, if any, research-based information played in developing it. The policy covered some highly contentious political issues, most prominently the issue of privatization of the fertilizer sector in place of the large-scale and long-standing subsidy program. How the actors engaged and appeased people with vested interests who would normally oppose the policy, and the degree to which research-based information played a role in policy development, is of interest to IFPRI and others engaged in policy research.